Unemployment Dynamics in the OECD - Elsby, Michael W. L.; Hobijn, Bart; Şahin, Ayşegül (The Review of Economics and Statistics, 2013)
We provide a set of comparable estimates for the rates of inflow to and outflow from unemployment using publicly available data for fourteen OECD economies. Using a novel decomposition that allows for deviations of unemployment from its flow steady state, we find that fluctuations in both inflow and outflow rates contribute substantially to unemployment variation within countries. Anglo-Saxon economies exhibit approximately a 15:85 inflow-outflow split to unemployment variation, while continental European and Nordic countries display closer to a 45:55 split. In all economies, increases in inflows lead increases in unemployment, whereas outflows lag a ramp-up in unemployment.